Dampak Membuang Sampah Sembarangan terhadap Kelestarian Lingkungan dan Ekonomi Beserta Sanksi terhadap Masyarakat yang Membuang Sampah Sembarangan Tempat (Studi Kota Bukittinggi) - Sabri, Sabri; Nasfi, Nasfi (Jurusan PIPS FKIP UMMY Solok, 2020)
With various kinds of progress in recent years, the City of Bukittinggi Government is still faced with various problems/problems, one of which is the problem of waste management and sanctions against people who dispose of littering places. This study examines the impact of littering on environmental sustainability and imposing sanctions on people who dispose of garbage carelessly